A Case of Infective Abdominal Aortic Aneurysm due to Haemophilus influenzae Type B - Sato, Toshimitsu; Kobayashi, Masayoshi (International Journal of Angiology, 2012)
Infective abdominal aortic aneurysm (IAAA) is relatively rare, but a case which is caused by Haemophilus influenzae type B is very rare. We experienced one IAAA case due to H. influenzae type B. The patient was 69-year-old man presenting with severe abdominal and back pain and elevated C-reactive protein (CRP), as inflammatory marker. The patient was found to have saccular aneurysm infrarenal aorta on computed tomography scanning. First, we started to treat him with antibiotic agent and second, we operated him at day 8 after admission with expanded polytetrafluoroethylene graft. Revascularization was made in situ reconstruction. As the result of culture with aneurysm wall, we found that the cause of this aneurysm was the infection of H. influenzae type B. As far as we know, this bacterium is scarcely reported as the cause of infective aortic aneurysms. We reported this IAAA case with the review of the English literature.
Keywords: abdominal aortic aneurysm; infection; mycotic aneurysm; polytetrafluoroethylene; C-reactive protein; in situ reconstruction; false aneurysm